Oily sand cleaning optimization by surfactants interfacial tension screening and hydrocyclone separation Pengoptimuman pembersihan pasir berminyak oleh saringan ketegangan antara muka surfaktan dan pemisahan hidrosiklon - Sidek, A. (Malaysian Society of Analytical Sciences, 2021)
The oily sand cleaning process should pass the standard discharge requirements so that its impact on the environment can be minimized. This work has used integrated surfactants which includes sodium dodecyl sulfate (SDS, anionic), saponin (plant-based, nonionic), and cetyl trimethylammonium bromide (CTAB, cationic) with hydrocyclone method, for washing oily sand (41 wt. of paraffin) with fixed cleaning time of 150 minutes. The interfacial tension (IFT) of the surfactants as a cleaning agent was screened based on the critical micelle concentration (CMC) so that the desirable surfactant concentration can be used. Field Emission Scanning Electron Microscopy-Energy Dispersive X-ray (FESEM-EDX) was used to characterize the sand for before and after the cleaning process. As compared to without hydrocyclone, the application of hydrocyclone caused in increasing oil removal efficiency with CTAB exhibits 91, followed by SDS (87), and saponin (79). Based on the FESEM-EDX characterization, besides its primary function of oil removal from the sand, saponin is also capable to remove heavy metal elements. It can be deduced that the integration of hydrocyclone with the surfactants can cause in synergized effects which could then improve the oily sand cleaning efficiency. Â© 2021, Malaysian Society of Analytical Sciences. All rights reserved.